From over to undercompensation: Variable responses to herbivory during ontogeny of a Neotropical monocarpic plant. (23rd May 2016) - Tito, Richard; Castellani, Tânia T.; Fáveri, Sarita B.; Lopes, Benedito C.; Vasconcelos, Heraldo L.
Abstract: Empirical and theoretical work has suggested that plants can change their compensatory responses to herbivory as they develop. However, such a relationship is likely to be more complex than previously thought since the amount and type of damage a plant receives can also change as the plant develops. Here, we determined the survival, growth, and reproductive output of plants ( Actinocephalus polyanthus ) from different ontogenetic stages that received variable levels of natural or simulated herbivore damage. Juvenile plants and non‐reproductive adults in which leaves were damaged showed full vegetative compensation, whereas pre‐reproductive plants were not able to replace the lost leaves. However, these same pre‐reproductive plants produced more inflorescences and thus more seeds and seedlings than control plants. In contrast, damage to vegetative and/or reproductive structures during the reproductive phase resulted in a negative effect on seed and seedling production. Herbivory effects on plant survival, growth, and reproduction during the vegetative and pre‐reproductive phases were independent of the amount of damage. However, during reproduction, the magnitude of these effects was strongly influenced by the amount of damage and the reproductive stage of the plant at the time of the damage. In short, our results demonstrate that the survival, growth, and reproductive responses to herbivory of A. polyanthus can be dependent on the timing and/or intensity of damage. The reproductive response of A. polyanthus to our simulated herbivory treatments during the pre‐reproductive phase represents an example of overcompensation. Furthermore, it indicates that vegetative regrowth is not necessarily a driving factor for tolerance.